2010
DOI: 10.1002/hbm.20887
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical differences in brain areas implicated in perceptual and other core features of autism revealed by cortical thickness analysis and voxel‐based morphometry

Abstract: Autism spectrum disorder is a complex neurodevelopmental variant thought to affect 1 in 166 [Fombonne (2003): J Autism Dev Disord 33:365-382]. Individuals with autism demonstrate atypical social interaction, communication, and repetitive behaviors, but can also present enhanced abilities, particularly in auditory and visual perception and nonverbal reasoning. Structural brain differences have been reported in autism, in terms of increased total brain volume (particularly in young children with autism), and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
194
3
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(235 citation statements)
references
References 74 publications
27
194
3
6
Order By: Relevance
“…Increased thickness and other structural atypicalities in the ACC were initially reported in post-mortem studies (Bailey et al, 1998;Kemper & Bauman, 1993). Previous structural MRI studies reported both decreased grey matter volume in the ACC (Abell et al, 1999;Kwon, Ow, Pedatella, Lotspeich, & Reiss, 2004;McAlonan et al, 2002), and increased thickness in this region in individuals with ASD relative to controls (Bonilha et al, 2008;Hyde et al, 2010;Schmitz et al, 2006;Toal et al, 2009), but there were no data on age-related changes in the ACC. The present study is important in its findings of developmental changes in cortical thickness in ASD in the rACC, a region central to the social cognitive functions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Increased thickness and other structural atypicalities in the ACC were initially reported in post-mortem studies (Bailey et al, 1998;Kemper & Bauman, 1993). Previous structural MRI studies reported both decreased grey matter volume in the ACC (Abell et al, 1999;Kwon, Ow, Pedatella, Lotspeich, & Reiss, 2004;McAlonan et al, 2002), and increased thickness in this region in individuals with ASD relative to controls (Bonilha et al, 2008;Hyde et al, 2010;Schmitz et al, 2006;Toal et al, 2009), but there were no data on age-related changes in the ACC. The present study is important in its findings of developmental changes in cortical thickness in ASD in the rACC, a region central to the social cognitive functions.…”
Section: Discussionmentioning
confidence: 95%
“…Some groups have reported increased thickness or density in brain regions in groups of pre-adolescents (Bonilha et al, 2008) and adults (Hyde, Samson, Evans, & Mottron, 2010;Schmitz et al, 2006;Toal et al, 2009) with ASD relative to typically developing individuals. As these prior studies focused on samples with narrower age ranges their results reflect alterations in brain morphology during restricted periods and are not able to examine developmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, individuals with ASD may have a reduced size, but increased number, of minicolumns (8), which could underpin differences in cortical surface area (9,10). Also, individuals with ASD may have an excess number of neurons in some brain regions (11), which in turn may affect measures of cortical thickness (9,12). Therefore, different morphometric features of the cortical surface provide proxy measures of various aspects of local gray-matter architecture.…”
mentioning
confidence: 99%
“…However, compared with FreeSurfer, GMVs based on VBM provide more precise measures of subcortical structures such as the basal ganglia [52,53] which may be one of the important etiological locations in schizophrenia. In addition, as suggested by…”
Section: Discussionmentioning
confidence: 99%